High-Resolution in vivo Imaging of Xylem-Transported CO2 in Leaves Based on Real-Time 11C-Tracing - Hubeau, Michiel; Thorpe, Michael R.; Mincke, Jens; Bloemen, Jasper; Bauweraerts, Ingvar; Minchin, Peter E. H.; De Schepper, Veerle; De Vos, Filip; Vanhove, Christian; Vandenberghe, Stefaan; Steppe, Kathy (Frontiers in Forests and Global Change, 2019)
Plant studies using the short-lived isotope 11C to label photosynthate via atmospheric carbon dioxide (CO2), have greatly advanced our knowledge about the allocation of recent photosynthate from leaves to sinks. However, a second source for photosynthesis is CO2 in the transpiration stream, coming from respiration in plant tissues. Here, we use in vivo tracing of xylem-transported 11CO2 to increase our knowledge on whole plant carbon cycling. We developed a new method for in vivo tracing of xylem-transported CO2 in excised poplar leaves using 11C in combination with positron emission tomography (PET) and autoradiography. To show the applicability of both measurement techniques in visualizing and quantifying CO2 transport dynamics, we administered the tracer via the cut petiole and manipulated the transport by excluding light or preventing transpiration. Irrespective of manipulation, some tracer was found in main and secondary veins, little of it was fixed in minor veins or mesophyll, while most of it diffused out the leaf. Transpiration, phloem loading and CO2 recycling were identified as mechanisms that could be responsible for the transport of internal CO2. Both 11C-PET and autoradiography can be successfully applied to study xylem-transported CO2, toward better understanding of leaf and plant carbon cycling, and its importance in different growing conditions.